Pengaruh Pembiayaan Bermasalah dan Kecukupan Modal Terhadap Profitabilitas: Studi Kasus Pada Bank Umum Syariah Yang Terdaftar di Otoritas Jasa Keuangan Periode 2016-2020 - Risdianti Risdianti; Wirman Munaraja (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2022)
This study aims to determine the Effect of Problematic Financing (NPF) and Capital Adequacy (CAR) on Profitability (ROA) in Islamic Commercial Banks for the Period 2016-2020. The population in this study is sharia commercial bank period 2016-2020. Sampling techniques use purposive sampling. The sample that met the research criteria was 11 banks. The data analysis methods used are descriptive analysis and multiple linear regressions. The results of this study stated that Problem Financing (NPF) has a negative effect on Profitability (ROA). Capital Adequacy (CAR) has a significant positive effect on Profitability (ROA).